1992
DOI: 10.1029/92gl01161
|View full text |Cite
|
Sign up to set email alerts
|

The effect of solar wind dynamic pressure changes on low and mid‐latitude magnetic records

Abstract: Magnetic records from low and mid latitude stations have been examined to determine their response to solar wind pressure changes. The best correlation between ground level changes and the change in the square root of the solar wind dynamic pressure occurs for stations at latitudes from 15° to 30° such as Tahiti, Honolulu, San Juan and Midway. The horizontal component of the field changes on average 16.5 nT for each change of 1(nPa)½ of the square root of dynamic pressure. This is 50% greater than the vacuum m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
99
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(109 citation statements)
references
References 9 publications
10
99
0
Order By: Relevance
“…As a consequence, on the ground a sudden impulse (SI) in the geomagnetic field is observed which, at middle and low latitudes, typically involves a step-like variation of the northsouth component H whose amplitude has been found to be roughly proportional to the change of the square root of the SW dynamic pressure [Siscoe et al, 1968;Ogilvie et al, 1968;Su and Konradi, 1975]. Sis recorded by ground magnetometers at geomagnetic latitudes between 15 ø and 30 ø have been analyzed by Russell et al [1992Russell et al [ , 1994 :40), the sense of polarization of low-frequency geomagnetic field fluctuations (0.8-3.6 mHz) is CCW in the morning and reverses to CW in the afternoon but the reversal is delayed by a few hours with respect to local noon; we explained this feature, suggesting that the observed waves could be mostly generated by SW discontinuities impacting the magnetopause in the early afternoon sector, as expected for corotating interplanetary structures [see Rostoker and Sullivan, 1987], rather than by the Kelvin-Helmholtz instability, whose effects at our latitude are strongly damped [Yurnoto, 1986].…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, on the ground a sudden impulse (SI) in the geomagnetic field is observed which, at middle and low latitudes, typically involves a step-like variation of the northsouth component H whose amplitude has been found to be roughly proportional to the change of the square root of the SW dynamic pressure [Siscoe et al, 1968;Ogilvie et al, 1968;Su and Konradi, 1975]. Sis recorded by ground magnetometers at geomagnetic latitudes between 15 ø and 30 ø have been analyzed by Russell et al [1992Russell et al [ , 1994 :40), the sense of polarization of low-frequency geomagnetic field fluctuations (0.8-3.6 mHz) is CCW in the morning and reverses to CW in the afternoon but the reversal is delayed by a few hours with respect to local noon; we explained this feature, suggesting that the observed waves could be mostly generated by SW discontinuities impacting the magnetopause in the early afternoon sector, as expected for corotating interplanetary structures [see Rostoker and Sullivan, 1987], rather than by the Kelvin-Helmholtz instability, whose effects at our latitude are strongly damped [Yurnoto, 1986].…”
Section: Introductionmentioning
confidence: 99%
“…As previously stated, the general aspects of the asymptotic variation have been currently investigated considering the geomagnetic response of the H component approximately 10 min after the peak response (Russell et al, 1992(Russell et al, , 1994aRussell and Ginskey, 1995;. In order to allow for a comparison with previous investigations, we conducted a similar analysis considering the difference between the 10-min average, 16:05-16:15 UT, and H E .…”
Section: An Analysis Of the Geomagnetic Responsementioning
confidence: 99%
“…Specific attention has been addressed in the scientific literature to the local time dependence of the geomagnetic response. Statistical analysis revealed that the asymptotic response of the H component shows at low latitudes (15 • -30 • ) a weak MLT dependence (MLT being the magnetic local time), with maximum values around local noon, minimum values around midnight, and an average value of ∼16.5 nT/(nPa) 1/2 (Russell et al, 1992(Russell et al, , 1994a. At subauroral latitudes (∼54 • -58 • ), the asymptotic response shows a different pattern, with strongly depressed (and even negative) values in the morning, and enhanced values in the afternoon (∼30 nT/(nPa) 1/2 ; Russell and Ginskey, 1995).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They determined, in both seasons, a maximum near midnight, a minimum at 7-8 LT, and a secondary maximum on the dayside; in addition, the amplitude of the LT modulation was much larger in the summer (approximately by a factor ≈3). Russell et al (1992Russell et al ( , 1994a reported that at low and middle latitudes  is maximum around noon during northward IMF conditions; in addition,  was found to decrease in the daytime sector and to enhance significantly in the night time sector in the case of southward IMF. At 36°, Francia et al (2001) revealed a LT dependence of the relative response, R H =/P 1/2 , characterized by a depressed value in the morning (10 nT/(nPa) 1/2 ), a greater amplitude in the evening and night sector (14-17 nT/(nPa) 1/2 ), and a maximum after the local noon (20 nT/(nPa) 1/2 ).…”
Section: The General Aspects and The Local Time Dependencementioning
confidence: 99%